Influence of Long-term Volume Therapywith Hydroxyethyl Starch on Leukocytes in Patients with Acute Stroke - Woessner, Ralph; Grauer, Markus T.; Dieterich, Hans-Jürgen; Treib, Wolfgang; Stoll, Martin; Treib, Johannes (Arzneimittelforschung, 2003)
A repeated administration of hydroxyethyl starch affects hemostasiological and rheological factors such as the concentration of factor VIII/von Willebrand factor, platelet volume and plasma viscosity. An earlier study showed that HES also lowers the concentration of fibronectin, a molecule important in the reticuloendothelial system (RES). RES has a “clearing function” and is a part of the non-immune-specific defense mechanisms of the body. It is involved in the elimination of HES from the blood. Since leukocytes are another important part of the unspecific defense system, the goal of the present study was to investigate whether HES affects leukocytes. After giving their informed consent, 20 patients with cerebral perfusion disorders were randomized and underwent a doubleblind 10-day hypervolemic hemodilution with HES 200/0.5/13 or HES 70/0.5/4. The numbers of leukocytes, percentage of lymphocytes, percentage of neutrophilic granulocytes and hemoglobin concentration were measured. The absolute number of leukocytes did not change significantly, but the share of neutrophilic granulocytes increased. The increase in neutrophilic granulocytes reflects an increase in phagocytic activity. HES 200/0.5/13, which has the larger in vivo molecular weight (MW = 95 kD), caused a larger increase in neutrophilic granulocytes than HES 70/0.5/4, which has an in vivo MW of 58 kD.
Keywords: CAS 9005-27-0; Hydroxyethyl starch, acute stroke, effect on leukocytes, effect on fibronectin